2021
DOI: 10.1007/s00265-021-02996-4
|View full text |Cite
|
Sign up to set email alerts
|

Individual behavioural traits not social context affects learning about novel objects in archerfish

Abstract: Learning can enable rapid behavioural responses to changing conditions but can depend on the social context and behavioural phenotype of the individual. Learning rates have been linked to consistent individual differences in behavioural traits, especially in situations which require engaging with novelty, but the social environment can also play an important role. The presence of others can modulate the effects of individual behavioural traits and afford access to social information that can reduce the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…While less is known about cognition in fishes than in mammals, the field is growing. Fish are capable of all the main kinds of learning identified in mammals [ 78 , 79 , 80 , 81 , 82 , 83 ], with individual differences in learning capacity [ 74 , 84 , 85 , 86 , 87 ] and possible relationships with personality. Looking at the relationship between the shy-bold continuum and learning, research has shown, for example, that shy brook trout were better at learning to navigate a maze than were bold brook trout [ 88 ], that bold sea trout were better at learning to avoid parasites [ 89 ], and that bold zebrafish and guppies showed better inhibition in a tube task [ 90 ].…”
Section: Fishes Are Individuals: Implications For Welfare In An Aquac...mentioning
confidence: 99%
“…While less is known about cognition in fishes than in mammals, the field is growing. Fish are capable of all the main kinds of learning identified in mammals [ 78 , 79 , 80 , 81 , 82 , 83 ], with individual differences in learning capacity [ 74 , 84 , 85 , 86 , 87 ] and possible relationships with personality. Looking at the relationship between the shy-bold continuum and learning, research has shown, for example, that shy brook trout were better at learning to navigate a maze than were bold brook trout [ 88 ], that bold sea trout were better at learning to avoid parasites [ 89 ], and that bold zebrafish and guppies showed better inhibition in a tube task [ 90 ].…”
Section: Fishes Are Individuals: Implications For Welfare In An Aquac...mentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that archerfish can learn complex sensorimotor skills simply by observing the actions of other group members, without the need to practice themselves 42 . Some studies 48 even found that archerfish are sensitive to the presence of an audience while foraging (e.g., the audience has an impact on how long it takes archerfish to shoot, but also see 49 , which did not find any effect of the social context on archerfish learning rates). Establishing whether the competitive archerfish exhibit prosocial behavior could shed light whether even a competitive species, with no grouping preference 34 , would demonstrate this kind of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in European starlings (Sturnus vulgaris), dominant individuals are less neophobic and thus learn a novel task quicker than subordinate group members (Boogert, Reader, & Laland, 2006) while in jackdaws (Corvus monedula), dominant individuals are far more likely to monopolize resources leaving little opportunity for subordinates to learn individually (Federspiel, Boeckle, von Bayern, & Emery, 2019). However, in archerfish (Toxotes chatareus), only the personalities of individuals predict their learning propensity and not the social ranks (Jones, Spence-Jones, Webster, & Rendell, 2021). Within an individual, the choice between asocial learning, social learning, and innovation is flexible.…”
Section: Introductionmentioning
confidence: 99%